Structural Teaching of Basic Practice of Writing a Publication to Young Writers of a Public Elementary School - Apolonio, Edmelyn V. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study intends to enhance writing skills among young writers in a public elementary school through the structural teaching basic practice of writing a publication. Effective expression of one's own views, opinions, ideas, and values on a certain subject through writing using one's own language is a skill that should be nurtured in school for every student. This study used a descriptive research design, and the participants were 35 students from a public elementary school. Qualitative data were gathered through the use of questionnaires with pretest and post-test to analyze whether the implementation of structural teaching basic practice of writing a publication to young writers of public elementary school was effective in improving the students' writing skills. The study revealed the skills that most of the grade 4, grade 5 and grade 6 students have not yet mastered are the following: writing an explanation, talks, commenting on an issue and an opinion on an issue (97.14%); writing scripts for radio broadcasting and writing short news, editorials, and other parts of the newspaper (100%); writing a report, sports news, letter to the editor, script for radio broadcasting (100%) respectively. Descriptive statistics were used to interpret data gathered. The students got a pretest mean score of 11.63 with a standard deviation of 0.55 and a post-test mean score of 25.66 with a standard deviation of 0.51. It is evident that there is an increase in mean score of +14.03 between pre and post-tests, from 11.63 to 25.66. The participants' pre-test and post-test differences are very significant based on the computed t-value of 29.08 0.05 level of significance. It is important to note that the use of structural teaching basic practice of writing a publication to young writers has improved their skills in writing.